2002
DOI: 10.1063/1.1517724
|View full text |Cite
|
Sign up to set email alerts
|

Field emission properties of porous diamond-like films produced by chemical vapor deposition

Abstract: The field emission properties of “porous diamond-like” carbon structures have been characterized. A hot filament chemical vapor deposition system fed with ethyl alcohol vapor diluted in helium was used to deposit the samples. Morphological analysis by field emission scanning electron microscopy revealed that they had a highly porous structure, which was attributed to the modification of the kinetics of the carbon deposition process due to the presence of helium as a buffer gas. Micro-Raman spectroscopy showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…The results obtained here are different from that reported before [18]. In that paper, the carbon nanotubes are pulled up to align their main longitudinal axis with the externally applied electric field vector during the rise sweep.…”
contrasting
confidence: 80%
“…The results obtained here are different from that reported before [18]. In that paper, the carbon nanotubes are pulled up to align their main longitudinal axis with the externally applied electric field vector during the rise sweep.…”
contrasting
confidence: 80%
“…8,[13][14][15][16] There have been several observations of hysteresis in the FE data of CNT arrays, porous diamond like fibers, CNT fibers (CNFs), and graphene films. [17][18][19] The onset of hysteresis has been linked to various phenomena, such as emission via intermediate electron energy states for nanocarbon films 20 and the electrostatic alignment of various atomic and radical species on the emitting surface of porous diamond-like carbon 21 and adsorption/desorption effects in CNTs. 17,21,22 It has been shown that hysteresis in the FE data depends on gas exposures, growth conditions, and conditions of the cathode materials.…”
mentioning
confidence: 99%
“…The origin of the field emission hysteresis behavior has been speculated to be due to several different factors, such as emission via intermediate electron energy states in the nanocarbon films, electrostatic alignment of the terminating species, capture of carriers by deep levels for wide-band-gap semiconductors, and adsorption/desorption of gaseous molecules454647. However, the J-E curve of the T-ZnO/rGO nanostructure-based field-emission device with ITO glass as an anode shows no hysteresis (Fig.…”
Section: Resultsmentioning
confidence: 99%